2000
DOI: 10.1108/09654280010320901
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned: working towards the National Healthy School Standard

Abstract: As part of the work leading to the development of the National Healthy Schools Scheme, an audit was carried out of existing healthy schools schemes in England. This, together with an evaluation of healthy schools activities within eight pilot healthy schools partnerships throughout England funded by the Department of Health and the Department for Education and Employment, formed part of the research underpinning the creation of a National Healthy Schools Standard. Principles for effective working are identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…These findings are consistent with the evidence which shows that the participation of teachers, family, community members, and students in the design and implementation of the programme, and the use of participatory, active learning techniques where young people have the opportunity to practice or demonstrate specific skills, are key drivers of the acceptability and feasibility of a school health promotion intervention [7]. Similarly, individuals who strongly support and advocate for a programme have often been cited by the education and health agencies as among the primary reasons they have been able to implement innovative programmes [35][36][37][38]; in our study, the leadership of school principals was a key factor in the successful implementation of the intervention and facilitating the engagement of the wider school community.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the evidence which shows that the participation of teachers, family, community members, and students in the design and implementation of the programme, and the use of participatory, active learning techniques where young people have the opportunity to practice or demonstrate specific skills, are key drivers of the acceptability and feasibility of a school health promotion intervention [7]. Similarly, individuals who strongly support and advocate for a programme have often been cited by the education and health agencies as among the primary reasons they have been able to implement innovative programmes [35][36][37][38]; in our study, the leadership of school principals was a key factor in the successful implementation of the intervention and facilitating the engagement of the wider school community.…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, school-based health promotion programs and policies are increasingly considered to be an important opportunity to reduce health problems in youngsters (Allensworth 1993;St.Leger 1999;Aggleton et al 2000;Inchley et al 2000;Moon 2000;Parsons 2002;St.Leger 2004;Gabhainn et al 2007). In the Netherlands schools are autonomous regarding their health promotion policy.…”
Section: Introductionmentioning
confidence: 99%
“…Another found similarly the wider school environment largely neglected in teachers’ discussions [14]. Some authors have found teachers to view health promotion as outside the core business of schools [15], though other studies have found the opposite, provided leadership and policy is supportive [16]. As the professionals who coach young people, teachers’ perspectives are arguably crucial to the development of school health policy.…”
Section: Introductionmentioning
confidence: 99%